The Pilot Study of Fibrin with Temporomandibular Joint Derived Synovial Stem Cells in Repairing TMJ Disc Perforation. (15th April 2014) - Wu, Yang; Gong, Zhongcheng; Li, Jian; Meng, Qinggong; Fang, Wei; Long, Xing
Abstract : TMJ disc related diseases are difficult to be cured due to the poor repair ability of the disc. TMJ-SDSCs were ideal cell sources for cartilage tissue engineering which have been widely used in hyaline cartilage regeneration. Fibrin gel has been demonstrated as a potential scaffold for neocartilage formation. The aim of this study was to repair the TMJ disc perforation using fibrin/chitosan hybrid scaffold combined with TMJ-SDSCs. Rat TMJ-SDSCs were cultured on hybrid scaffold or pure chitosan scaffolds. The cell seeding efficiency, distribution, proliferation, and chondrogenic differentiation capacity were investigated. To evaluate the in vivo repair ability of cell/scaffold construct, rat TMJ disc explants were punched with a defect to mimic TMJ disc perforation. Cell seeded scaffolds were inserted into the defect of TMJ disc explants and then were implanted subcutaneously in nude mice for 4 weeks. Results demonstrated that fibrin may improve cell seeding, proliferation, and chondrogenic induction in vitro . The in vivo experiments showed more cartilage ECM deposition in fibrin/chitosan scaffold, which suggested an enhanced reparative ability. This pilot study demonstrated that the regenerative ability of TMJ-SDSCs seeded in fibrin/chitosan scaffold could be applied for repairing TMJ disc perforation.